Protective Effects of Complement Component 8 Gamma Against Blood-Brain Barrier Breakdown - Kim, Jong-Heon; Han, Jin; Suk, Kyoungho (Frontiers in Physiology, 2021)
The bloodbrain barrier (BBB) regulates the traffic of micromolecules and macromolecules between the peripheral blood and the central nervous system, to maintain brain homeostasis. BBB disruption and dysfunction accompany a variety of neurological disorders and are closely related with the neuroinflammatory cascades that are triggered by leukocyte infiltration and glial activation. Here we explored the role of complement component 8 gamma (C8G) in the maintenance of BBB integrity. Previously, C8G was shown to inhibit neuroinflammation by interfering with the S1PS1PR2 interaction. The results of the present study revealed that C8G is localized in perivascular astrocytes, whereas S1PR2 is expressed in endothelial cells (ECs). In the lipopolysaccharide-induced neuroinflammation model, the intracerebroventricular administration of the recombinant C8G protein protected the integrity of the BBB, whereas shRNA-mediated C8G knockdown enhanced BBB permeability and neutrophil infiltration. Using pharmacological agonists and antagonists of S1PR2, we demonstrated that C8G inhibited the inflammatory activation of ECs in culture by antagonizing S1PR2. In the in vitro BBB model, the addition of the recombinant C8G protein preserved endothelial integrity, whereas the knockdown of C8G exacerbated endothelial leakage under inflammatory conditions. Together, our findings indicate an important role for astrocytic C8G in protecting the BBB in the inflamed brain, suggesting a novel mechanism of cross talk between astrocytes and ECs in terms of BBB maintenance.